Flux data of total mass, particulate organic carbon, and zooplankton fecal pellet of time-series sediment trap samples at moorings TJ-W1 and TJ-W2 in the western South China Sea - Junyuan Cao; Zhifei Liu; Baozhi Lin; Yulong Zhao (PANGAEA, 2024)
This dataset includes total mass flux (TMF, mg m-2 d-1), particulate organic carbon (POC) content (%), POC flux (mg C m-2 d-1), fecal pellet numerical flux (pellets m-2 d-1), and fecal pellet carbon (FPC) flux (mg C m-2 d-1) of time-series sediment trap samples at 500 m and 1170 m water depth of the mooring TJ-W1 and 1380 m water depth of the mooring TJ-W2 in the western South China Sea from May 2021 to May 2022. A total of 63 samples were obtained (21 samples from each water depth) for this dataset. TMF of sediment trap samples was derived when the dry weight (mg) was divided by the collecting area (0.5 m2) and collecting time (17 days). POC content of sediment trap samples was measured by a Cario EL Cube elemental analyzer at the Third Institute of Oceanography, Ministry of Natural Resources, with a precision of better than ±0.02% (SD, 1σ; n = 2). POC flux was calculated by the product of the TMF and POC content. Zooplankton fecal pellets in the sinking particles were observed under a Zeiss Stemi 508 stereomicroscope coupled to a Zeiss Axiocam 305 digital camera at the State Key Laboratory of Marine Geology, Tongji University. Fecal pellets were identified, counted, and measured according to three shapes: ellipsoidal, cylindrical, and spherical, and each shape was counted and measured separately using the Fiji software. The biovolumes of the three fecal pellet shapes were calculated from the formulas for ellipsoid, cylinder, and sphere, respectively. The biovolume-carbon content conversion factor used is 0.036 mg C mm-3 for all pellets. Fecal pellet numerical and carbon fluxes were obtained when the pellet number and carbon content were divided by the collecting area (0.5 m2) and collecting time (17 days).